Extraction of a temporal conceptual model from a relational database. (1st January 2013) - Hoang, Quang; Nguyen, Van Toan
Related to the problem of temporal database design, a relational target model has been designed from a temporal conceptual model. Extraction of the temporal conceptual model from a relational model is called the reverse engineering of the relational model. Solving this problem will facilitate an upgraded temporal information system. In this research, we construct a conceptual model which has been used to design the temporal relational model. This approach of extraction is based on characteristics of the set of attributes, the primary key, and the set of foreign keys of the relational schema in the temporal relational model. Thereby, we propose conversion rules relating to the identification of the components existing within the temporal conceptual model accordingly.